Use of Extracorporeal Membrane Oxygenation as Bridge to Replacement Therapies in Cardiogenic Shock: Insights From the Extracorporeal Life Support Organization. (9th December 2021) - Mastoris, Ioannis; Tonna, Joseph E.; Hu, Jinxiang; Sauer, Andrew J.; Haglund, Nicholas A.; Rycus, Peter; Wang, Yu; Wallisch, William J.; Abicht, Travis O.; Danter, Matthew R.; Tedford, Ryan J.; Fang, James C.; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: There has been increasing use of extracorporeal membrane oxygenation (ECMO) as bridge to heart transplant (orthotopic heart transplant [OHT]) or left ventricular assist device (LVAD) over the last decade. We aimed to provide insights on the population, outcomes, and predictors for the selection of each therapy. Methods: Using the Extracorporeal Life Support Organization Registry between 2010 and 2019, we compared in-hospital mortality and length of stay, predictors of OHT versus LVAD, and predictors of in-hospital mortality for patients with cardiogenic shock that were bridged with ECMO to OHT or LVAD. One hundred sixty-seven patients underwent LVAD versus 234 patients who underwent OHT. Results: The overall use of ECMO has increased from 1.7% in 2010 to 22.2% in 2019. Mortality was similar between groups (LVAD: 28.7% versus OHT: 29.1%) while length of stay was longer for OHT (LVAD: 49.6 versus OHT: 59.5 days, P =0.05). Factors associated with OHT included prior transplant (odds ratio [OR]=31.26 [CI, 3.84–780.5]), use of a temporary pacemaker (OR=6.5 [CI, 1.39–50.15]), and increased use of inotropes on ECMO (OR=3.77 [CI, 1.39–11.07]), whereas LVAD use was associated with weight (OR=0.98 [CI, 0.97–0.99]), cardiogenic shock presentation (OR=0.40 [CI, 0.21–0.78]), previous LVAD (OR=0.01 [CI, 0.0001–0.22]), respiratory failure (OR=0.28 [CI, 0.11–0.70]), and milrinone infusion (OR=0.32 [CI, 0.15–0.67]). Older age (OR=1.07 [CI, 1.02–1.12]), cannulation bleeding (OR=26.1 [CI, 4.32–221.3]), and surgical bleeding (OR=6.7 [CI, 1.26–39.9]) in patients receiving LVAD and respiratory failure (OR=5 [CI, 1.17–23.1]) and continuous renal replacement therapy (OR=3.82 [CI, 1.28–11.9]) in patients receiving OHT were associated with increased mortality. Conclusions: ECMO use as a bridge to advanced therapies has increased over time, with more patients undergoing LVAD than OHT. Mortality was equal between the 2 groups while length of stay was longer for OHT.